Historiographic balance of the Health History Group in Boyacá-UPTC around the Bicentennial (2021)
This article makes a historiographic balance of the Health History Research Group in Boyacá from the Pedagogical and Technological University of Colombia in Tunja, around the theme of the Bicentennial celebration of the Independence of Colombia between 2008 and 2021. The proposed reflection encompasses the forms of articulation and consolidation of research in the sociocultural history of medicine and health. This theme is studied by a regional research group which is based on a conjunctural theme ―the bicentennial― and the different research branches originating from this over time. The publications (~20), conferences, and exhibitions on the subject allow the expansion of academic networks and help achieve the social appropriation of knowledge of academic products which is one of the aims of the group through the Museum of the History of Medicine and Health of the UPTC.